1995
DOI: 10.1128/aac.39.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Corynebacterium species and other non-spore-forming gram-positive bacilli to 18 antimicrobial agents

Abstract: The susceptibilities of 265 strains of Corynebacterium species and other non-spore-forming gram-positive bacilli to 18 antimicrobial agents were tested. Most strains were susceptible to vancomycin, doxycycline, and fusidic acid. Corynebacterium jeikeium and Corynebacterium urealyticum were the most resistant organisms tested. Resistance to ␤-lactams, clindamycin, erythromycin, azythromycin, ciprofloxacin and gentamicin was common among strains of Corynebacterium xerosis and Corynebacterium minutissimum. Ampici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
118
3
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 32 publications
20
118
3
6
Order By: Relevance
“…Unlike earlier studies [6,8], in our study, C. jeikeium and C. seminale did not have low MICs of nitrofurantoin. Another discord with earlier reports was revealed in case of TMP/SMX that was highly active on the majority of the strains studied by us while weak or missing activity of it against C. striatum, C. jeikeium, D. hominis and T. otitidis has been described [18][19][20].…”
Section: Mic (μG/ml)contrasting
confidence: 54%
See 3 more Smart Citations
“…Unlike earlier studies [6,8], in our study, C. jeikeium and C. seminale did not have low MICs of nitrofurantoin. Another discord with earlier reports was revealed in case of TMP/SMX that was highly active on the majority of the strains studied by us while weak or missing activity of it against C. striatum, C. jeikeium, D. hominis and T. otitidis has been described [18][19][20].…”
Section: Mic (μG/ml)contrasting
confidence: 54%
“…Our data corresponds to several studies that have shown high resistance of coryneforms to macrolides and lincosamines [6,7,15,17,18] and there is a distinct resistance pattern, MLSb (a co-occurring resistance to Macrolide, Lincosamine and Streptogramin B) [8]. In our study, 16 strains (13 C. seminale, 2 Cellulomonas/Microbacterium sp.…”
Section: Mic (μG/ml)mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the absence of accepted breakpoints for coryneform bacteria to interpretative categories, those established for Kirby-Bauer disk diffusion method by the NCCLS for organisms other than Haemophilus species and Neisseria gonorrhoeae were used by the authors. The breakpoints for Staphylococcus aureus were considered in the cases of penicillin, oxacillin and ampicillin (9,13,22,23).…”
Section: Antimicrobial Susceptibility Assaysmentioning
confidence: 99%